A platform-based strategic design approach for universal products. (10th November 2010) - Moon, Seung Ki; McAdams, Daniel A.
In this paper, we extend concepts from product family and platform design and mass customisation to create a method for a universal product family design. The objective of this paper is to develop a universal design method to generate an economically feasible design concept and evaluate the design feasibility with respect to disabilities within a product family in uncertain market environments. We consider a platform-level problem as a module selection problem for determining design parameters in variant modules for unique or common modules by minimising the production cost and maximising accessibility in a universal product family. In particular, a Bayesian game is employed to model uncertain situations regarding market environments. The proposed method is used to decide strategic equilibrium solutions for selecting modules in the universal product family being designed. To demonstrate implementation of the proposed method, we use a case study involving a family of kitchen products.